Keadilan Hak Asasi Manusia dalam Aksi Kamisan di Indonesia - Sabit Irfani; Ricky Santoso Muharam; Sunarso Sunarso (Badan Penelitian dan Pengembangan Hukum dan HAM, 2022)
The study aims to analyze “Thursday’s struggle for action” in seeking justice for human rights. This research is a type of descriptive research with a qualitative approach. Techniques used to collect data uses observations, interviews, and searches of documents and archives. The subject of this study is a “Thursday Action” and determination of the study subject using Purposive. This study shows the struggle of the victims’ families who never get tired, showing their longing related to the clarity provided by the government. Komnas HAM has recommended that there have been human rights violations against various cases of disappearances and acts of violence. There are indications that the perpetrators of human rights violations are not ordinary people. The state’s commitment to resolving cases of human rights violations is a key variable in resolving stalled cases in the Attorney General’s Office.